Sustainability assessment of community-based water resource management of irrigation systems for agriculture - Huong, Huynh Thi Lan; Anh, Pham Ngoc (Vietnam Journal of Science, Technology and Engineering, 2021)
To study community-based water resource management (CbWRM) of irrigation for agriculture, the participation of the community in the management of the irrigation system must be considered. CbWRM is the cooperation between a farming organization (the water-using cooperative group) and staterelated organizations (such as the Department of Water Resources Management and commune-level authorities) in the process of the operation and management of water. In the CbWRM model, the community participates in the selection and election of the management board, meetings to collect ideas to build a CbWRM model, and financial contributions to water use fees. The community also participates in the annual operational planning of water use. Therefore, this study aimed to develop indicators to assess the sustainability of the CbWRM model of irrigation for agriculture in the Hau Giang province, Vietnam. With an assessment result of 0.54 (relatively sustainable), this study shows a picture of water resource management in general and community participation in particular. These research results can help managers and policymakers promote community participation to achieve high-efficiency water resource management in the agriculture of the Hau Giang province.